number in an element industrial design (Journal of the College of Basic Education, 2022)
The study of the number in design is one of the important studies that gives the emerging and professional designer technical and philosophical mechanisms to understand the number and how to use it in designing products. Most of the design books and literature did not deal with the number as an element of the design, but rather dealt with the number as a design output while it is an indispensable element The same is true of common design elements, such as color, texture, and shape. The research aimed to reach that the number is one of the optical and perceptual elements of the industrial design, and the research was determined by using samples of means of communication and watches. The goal of the product and not attending it is not attending the product.